FUNDEF - 2000 a 2003: impactos dos gastos nos municípios do Estado do Ceará - Alencar Neto, João Lucio de (2007)
This paper presents a study on the resources of the FUNDEF, its institutionality and how resources are collected and contributed to the States and Municipalites. The study examines the gain as the Financing Federal Government from 1998 (FUNDEF), and some important aspects of this in Act Guidelines and Base Education Brasileira(LDB).In addition to these elements, the survey include a descriptive study, analyzing the results of spending resources of associated with educational indicators such as: number of funcions teaches in the years de 2000 to 2003. The most relevant results of the survey shwed that the funds received through the FUNDEF, even in Lange contributions educational indicators little changed, possibly by misuse. Focalizando the municipalities of the state of Ceará that received Lange amounts of resources, and that the contracts were intended for teaches functions, reproduced at what happerned in the vast majority of municipalities in the country, thas is, hiring of labour- disqualified.